the digital identity of Damascus university students on social Networks (Damascus University Journal of arts and humanities sciences, 2023)
The researcher aimed to explore features of the digital identity of Damascus university students on social Networks, and knowing the reasons of using pseudo digital identities from their point of view, as well as knowing the mechanism of their connection with others while using the social media. The researcher relied on the survey method and its field tool is the questionnaire that has been distributed on a quota sample of 100 individuals from Damascus University students in various theoretical and applied faculties. The study has reached a set of results, including: %86 of the sample’s individuals use their real identity on social media, in addition to lack ofdifferences which statistically indicate among the features of the digital identity of the sample's individuals on social media in the demographic variables (sex – age - type of college - income).
Keywords: digital identity; Damascus University students; social media